2010
DOI: 10.1073/pnas.1007862108
|View full text |Cite
|
Sign up to set email alerts
|

Active scaffolds for on-demand drug and cell delivery

Abstract: Porous biomaterials have been widely used as scaffolds in tissue engineering and cell-based therapies. The release of biological agents from conventional porous scaffolds is typically governed by molecular diffusion, material degradation, and cell migration, which do not allow for dynamic external regulation. We present a new active porous scaffold that can be remotely controlled by a magnetic field to deliver various biological agents on demand. The active porous scaffold, in the form of a macroporous ferroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
497
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 600 publications
(502 citation statements)
references
References 54 publications
4
497
0
1
Order By: Relevance
“…A key event leading to fibrous capsule formation is the adhesion of profibrotic macrophages, foreign body giant cells, and fibroblasts to the implant surface, as these cells secrete proteins that modulate fibrosis and increase collagen deposition (35,36). Previous in vitro experiments have demonstrated significant fibroblast and myoblast cell expulsion from RGD peptide-containing ferrogels in vitro, even with stimulation patterns shorter and less frequent than used here (30,31). It is possible that invading cells near the scaffold edges were expelled from the ferrogel system upon stimulation, because of fluid convection resulting from large gel deformations, leading to an overall diminished cell presence within the scaffold.…”
Section: Markers Of Muscle Regeneration: Centrally Located Nuclei Andmentioning
confidence: 99%
See 1 more Smart Citation
“…A key event leading to fibrous capsule formation is the adhesion of profibrotic macrophages, foreign body giant cells, and fibroblasts to the implant surface, as these cells secrete proteins that modulate fibrosis and increase collagen deposition (35,36). Previous in vitro experiments have demonstrated significant fibroblast and myoblast cell expulsion from RGD peptide-containing ferrogels in vitro, even with stimulation patterns shorter and less frequent than used here (30,31). It is possible that invading cells near the scaffold edges were expelled from the ferrogel system upon stimulation, because of fluid convection resulting from large gel deformations, leading to an overall diminished cell presence within the scaffold.…”
Section: Markers Of Muscle Regeneration: Centrally Located Nuclei Andmentioning
confidence: 99%
“…Previously, it has been demonstrated that magnetically responsive biomaterials termed ferrogels are capable of rapid, on-demand deformations in response to externally applied magnetic fields (30,31). In particular, ferrogels containing an iron oxide gradient (biphasic ferrogels) possess a capacity for large, fatigue-resistant deformations even at device sizes appropriate for small animal implantation.…”
Section: Significancementioning
confidence: 99%
“…In addition, the porous structure (size and shape) of the polymer network can be tuned by varying the freezing conditions and concentration of the cross-linker in the case of cryogels. [5,6] However, several disadvantages can be identified. Matrigel is often poorly chemically defined and thus culture-to-culture variation has been observed.…”
Section: Carbon Scaffolds For Neural Stem Cell Culture and Magnetimentioning
confidence: 99%
“…Recent examples include Fe 3 O 4 /alginate composite scaffolds delivering cells and drugs in response to variable magnetic forces2 and bacterial mechano‐sensitive channels acting like a dual‐control gate by cell membrane tension and MscL charges to modulate the delivery of bioactive molecules into live cells 20. These strategies, however, are not applicable in achieving ultrahigh release precision in ceramic‐based porous scaffolds due to the high rigidity, limited biodegradability, and large interconnected pores of ceramic scaffolds.…”
mentioning
confidence: 99%
“…The high resilience of CCS, on the other hand, allows the formation of strong water convection and shear force in the structure when compressed,2 assisting the release of cargos. Theoretically, the cargo release capability enabled by fluid convection should be a function of the counter pressure applied to squeeze the fluid out of the pores against capillary pressure.…”
mentioning
confidence: 99%